Magnetohydrodynamic Natural Convection Flow on a Sphere in Presence of Heat Generation - Molla, Md. M.; Taher, M. A.; Chowdhury, Md. M. K.; Hossain, Md. A. (Nonlinear Analysis: Modelling and Control, 2005)
The present work describes the effect of magnetohydrodynamic natural convection flow on a sphere in presence of heat generation. The governing boundary layer equations are first transformed into a non-dimensional form and the resulting nonlinear system of partial differential equations arethen solved numerically using the Keller-box method. Here we have focused our attention on the evolution of the surface shear stress in terms of local skin friction and the rate of heat transfer in terms of local Nusselt number, velocity distribution as well as temperature distribution for a selection of parameter sets consisting of heat generation parameter Q (= 0.0, 0.5, 1.0, 2.0) and the magnetic parameter M (= 0.0, 0.2, 0.5, 0.8, 1.0). Numerical solutions have been considered for Prandtl number Pr (= 0.7, 1.0, 2.0).